Quality assurance of spirometry for COPD clinic accreditation in Thailand - Pothirat C. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: To evaluate quality of spirometry for COPD clinic accreditation. Material and Method: A minimum of 25 spirograms from each of 38 hospitals were evaluated using the American Thoracic Society (ATS)/European Respiratory Society (ERS) acceptability criteria. Technicians were separated into two groups based on their respective level in spirometry training, previously trained-certified, and naïve (not formally trained-certified) groups. Unpaired t-test and Chi-square were used to compare differences between the two groups. Statistical significance was set at p < 0.05. Results: Thirty-eight technicians from 38 clinics submitted a total of 1,556 spirograms for accreditation evaluation. Of those, 1,066 (68.5%) spirograms met all ATS/ERS acceptability criteria. Only 47.4% of the clinics received an A grade. All clinics that received an A grade were staffed by trained-certified technicians. Significantly, more spirograms failed to meet the criteria from clinics with naïve technicians than clinics with trained-certified technicians (18.2% vs. 80.8%, p-value < 0.001). Criteria where the trained-certified group significantly achieved than naive group were satisfactory exhalation (93.4% vs. 20.9%, p-value < 0.001), no early termination (98.5% vs. 58.6%, p-value < 0.001), maximal effort throughout (96.2% vs. 89.1%, p-value < 0.001), and good start (91.6% vs. 79.9%, p-value < 0.001). Conclusion: Spirometry performed by the Thoracic Society of Thailand trained-certified technician was distinguishably higher quality than by a naïve technician. Our results are a reminder of the importance of quality assurance for spirometry in clinical practice.